If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -7) = 71 Reorder the terms: (-7 + 6x) = 71 Remove parenthesis around (-7 + 6x) -7 + 6x = 71 Solving -7 + 6x = 71 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6x = 71 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 71 + 7 6x = 71 + 7 Combine like terms: 71 + 7 = 78 6x = 78 Divide each side by '6'. x = 13 Simplifying x = 13
| 6-3x=5x-10x+15 | | c=5/9(30)(f-32) | | 9d-3=5d-9 | | -7/2a=21 | | 5/3x^2+6/x | | x+(x+1)+(x+2)=66 | | (8a^3/9b)(12b^2/16a) | | 36.7=42.42 | | 6+1.5y=5 | | 8*1(1/8) | | y+7/8=15/16 | | 63=13+u/9 | | n=8*1(1/8) | | 4w-7=3w | | 7+d/6=8 | | 3a+6a-1/2+1 | | X+1/x=10/3 | | X+1/x=10/3 | | 9y^3-21y^2-10y= | | 1+2x+3x^2+-4x^3+x^4=0 | | -m/5+8=10 | | 14x+7=8x+13 | | 5x-8=57 | | 10*(7/8)=n*2 | | -2(2r+5)= | | x=(4x^2-3)(4x^2+3) | | 6(x+7)-27= | | 2x+x+4/6=7 | | (x^2-2x-1)(x^2-2x-1)+(x^2-2x-1)+1=0 | | -4(5n-6)+4n= | | 1-3(n-5)=8 | | (x^2-2x-1)(x^2-2x-1)=0 |